Inside Back Cover: Biotechnology Journal 1/2020. Issue 1 (2nd January 2020) - Le, Kim; Tan, Christopher; Le, Huong; Tat, Jasmine; Zasadzinska, Ewelina; Diep, Jonathan; Zastrow, Ryan; Chen, Chun; Stevens, Jennitte
Abstract : The fully integrated Beacon cell culture system enables the manipulation, culturing and assaying of thousands of clones on a single nanofluidic chip. The Beacon platform allows for the generation of clonally derived cell lines of known phenotypic identity with a superior clonality data package, detailed tracking, rapid verification of clonal origin, and 99 % assurance of clonality. This is reported by Kim Le, Christopher Tan, Huong Le, Jasmine Tat, Ewelina Zasadzinska, Jonathan Diep, Ryan Zastrow, Chun Chen, and Jennitte Stevens in article 1900247 .